Anatomy of Anterolateral Ligament of Human Knee Joint: a Cadaveric Study at a Medical College in Kathmandu, Nepal - Kharbuja, Rabita; Chalise, Usha; Lama, Chhiring Palmu; Dhungel, Aryan (Nepal Medical College Journal, 2025)
Knee joint is a bicondylar variety of synovial joint formed by articulations among lower end of femur, upper end of tibia and patella. It is stabilized by numbers of ligaments, anterolateral ligament (ALL) being one of them. Recently, ALL is gaining researcher’s attention because of its discovery as a new ligament of knee joint which has a potential role in the anterolateral rotational stability. However, there is still persistence of different anatomical description of the ALL, including its prevalence, femoral origin, and tibial insertion. This study aimed to determine prevalence and detail anatomy of ALL in human knee joint. The study included 30 cadaveric lower limb of both side with intact knee joint available in Nepal Medical College, Department of Human Anatomy. ALL was identified in 26 knee joint (86.7%) where mean length of the ALL measured at extension and 90º flexion was 31.12± 8.06 mm and 32.59±7.71 mm respectively. The femoral attachment of ALL was variable; the most common one 42.31% being attached just posteroinferior to the lateral femoral epicondyle (LFE) followed by 38.46% attached to posterosuperior aspect of LFE and 19.23% of ALL attached just anteroinferior to LFE. The attachment of ALL on tibia was quantified relative to bony landmark; Gerdy’s tubercle (GT). The average distance between the GT and ALL attachment was found to be 21.82±4.89 mm. There is a need for detailed understanding of the ALL anatomy to ensure proper diagnosis and treatment of knee joint pathology.